ISO 22000 food safety : guidance and workbook for the manufacturing industry - Smith, David, 1942- (BSI, 2007)
"This book has been developed to provide support to manufacturing organizations in the implementation of an ISO 22000:2005 food safety management system. It is intended to be used by those charged with the implementation and running of the system in the manufacturing sector and will be found particularly helpful by members of the food safety team as well as departmental managers. The workbook is designed to be practical and easy-to-use, containing self-assessment checklists, handy tables and proformas along with useful extracts from the ISO 22000:2005 standard and a glossary of terms used. It also contains useful information on legal and regulatory issues and best practice."--Knovel.